2011
DOI: 10.1590/s0102-09352011000100032
|View full text |Cite
|
Sign up to set email alerts
|

Equações de predição para estimar valores da energia metabolizável de alimentos concentrados energéticos para aves utilizando meta-análise

Abstract: Equações de predição para estimar valores da energia metabolizável de alimentos concentrados energéticos para aves utilizando meta-análise RESUMOObtiveram-se equações de predição dos valores de energia metabolizável aparente corrigida (EMAn) para alimentos energéticos mais utilizados nas dietas de frangos de corte por meio do princípio da metaanálise. Foi realizada uma revisão bibliográfica de estudos realizados no Brasil para catalogar informações sobre valores de EMAn e composição química dos alimentos (PB; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
(5 reference statements)
1
3
0
2
Order By: Relevance
“…In the selected equations, the best fit was due to the higher adjusted R 2 and R 2 , in agreement with Nascimento et al (2011), who also reported an increase in R 2 with the increase in the number of variables in the equation. The use of prediction equations for ME of corn that are based on composition of DE was proposed by Noblet and Perez (1993) and Castilha et al (2011), although they used fewer variables.…”
Section: Resultssupporting
confidence: 86%
“…In the selected equations, the best fit was due to the higher adjusted R 2 and R 2 , in agreement with Nascimento et al (2011), who also reported an increase in R 2 with the increase in the number of variables in the equation. The use of prediction equations for ME of corn that are based on composition of DE was proposed by Noblet and Perez (1993) and Castilha et al (2011), although they used fewer variables.…”
Section: Resultssupporting
confidence: 86%
“…Durante muito tempo, prevaleceu a ideia de que a ave procura o alimento para satisfazer suas exigências em energia. No entanto, muitos trabalhos têm demonstrado que o controle do consumo de alimento é regulado pela densidade energética da ração (NASCIMENTO et al, 2011).…”
Section: Introductionunclassified
“…To obtain the equations via BN, data from the meta-analysis were used, referring to the experiments conducted in Brazil in the period from 1967 to 2007, resulting in 568 experiments ( Nascimento et al, 2009 ; Nascimento et al, 2011 ), among them which refer to the values of AMEn and chemical composition of energy ( n = 370) and protein ( n = 198) feedstuffs, of vegetable origin, commonly used in the formulation of broiler diets. The data used to validate the proposed equations were obtained by Alvarenga et al (2011) .…”
Section: Methodsmentioning
confidence: 99%
“… Zhao et al (2008) developed prediction equations using multiple regression to estimate the energy values using the chemical composition of the feedstuffs; however, their results have been inconsistent or applicable only to one feedstuff group ( Alvarenga et al, 2011 ). Nascimento et al (2009 , 2011 ) and Mariano et al (2012) used meta-analyses to better predict AMEn. Perai et al (2010) , Ahmadi et al (2007 , 2008 ), and Mariano et al (2013) used neural networks (NN), and the latter used a larger number of foods and in vivo trials.…”
Section: Introductionmentioning
confidence: 99%